ANALYSIS OF THE INFLUENCE OF ATTITUDES AND LEADERSHIP TRANSFORMATION ON LOYALTI AND EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE AT RSUP DR. SITANALA IN THE TIME OF A PANDEMIC - Channesya Meilinsye Sampetoding; Rian Adi Pamungkas; Rokiah Kusumapradja (Jurnal Cinta Nusantara (JCN), 2023)
Transformational leadership is characterized as a leader who focuses on achieving changes in the values, beliefs, attitudes, behavior, emotions, and needs of subordinates towards better changes in the future. This transformational leadership creates a positive attitude of employees and increases the motivation of employees. The existence of positive work motivation can improve employee performance which in turn affects employee loyalty. The purpose of this study was to analyze the effect of attitude and transformational leadership on employee loyalty and performance with work motivation as an intervening variable at RSUP dr. Sitanala in the Time of a Pandemic. This research is an explanatory research with a quantitative approach in the form of using causality hypotheses with a sample of 136. In this study, it was found that transformational attitudes and leadership have a positive effect on performance and loyalty through work motivation. Based on the analysis, the conclusions that can be put forward in this study are as follows: attitude and transformational leadership have a significant positive effect on employee loyalty and performance through work motivation. The implications of this research theoretically will prove the influence of research variables and managerially will further improve the leadership style and attitudes of employees in the hospital.